1995
DOI: 10.1002/ajh.2830500406
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic response of complement to heparin: Fluid‐phase generation of neoantigens in human serum and in a reconstituted alternative pathway amplification cycle

Abstract: We describe a study of the effects of heparin on complement activation through the use of assays for fragment C4d, fragment Bb, and the S-C5b-9 complex (S-MAC). In sera from healthy volunteers, virtually no change was observed in C4d either as a function of time or of heparin concentration, whereas changes in Bb and S-MAC were biphasic. This observation was explored in greater detail in the heparin concentration range 0.001-5.0 u/ml (5 x 10(-3) to 25 micrograms/ml). For both Bb and S-MAC, a significant (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Signaling in bone is dependent on the presence of LDL receptor-related protein 5 (LRP5), and mutations in this protein have recently been shown to be responsible for specific forms of high-bonemass trait and osteopenia, respectively [Boyden et al, 2002;Kato et al, 2002;Little et al, 2002]. Biphasic effects are not uncommon for heparin [Chevreuil et al, 1993;Keil et al, 1995;LaRochelle et al, 1999]. Regarding a single ligand-receptor system, low concentrations of heparin may facilitate the encounter of the growth factor with its signaling receptor by a ''reduced dimensionality'' mechanism [Lander, 1999], thus promoting the growth factor effect, whereas higher concentrations may be inhibitory due to a saturation of heparin-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling in bone is dependent on the presence of LDL receptor-related protein 5 (LRP5), and mutations in this protein have recently been shown to be responsible for specific forms of high-bonemass trait and osteopenia, respectively [Boyden et al, 2002;Kato et al, 2002;Little et al, 2002]. Biphasic effects are not uncommon for heparin [Chevreuil et al, 1993;Keil et al, 1995;LaRochelle et al, 1999]. Regarding a single ligand-receptor system, low concentrations of heparin may facilitate the encounter of the growth factor with its signaling receptor by a ''reduced dimensionality'' mechanism [Lander, 1999], thus promoting the growth factor effect, whereas higher concentrations may be inhibitory due to a saturation of heparin-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limitations with in vitro studies. Most anticoagulants such as Calcium chelators like ethylenediaminetetraacetic acid (EDTA), citrate, and heparin interact with complement activation as well as other biologic processes [22,23]. Recently, some authors reported using the thrombin-specific hirudin analog lepirudin as anticoagulant to study the role of complement in the inflammation [24].…”
Section: Discussionmentioning
confidence: 99%
“…The model allows crosstalk between all the inflammatory systems in whole blood, with the exception of thrombin which is inhibited by the anticoagulant, lepirudin (64). The advantage of lepirudin is that it does not interfere with other biological systems in particular not the complement system (64), in contrast to other anticoagulants like EDTA, citrate and heparin (169). The whole blood in vitro model allowed studies on cytokine production and inhibition (study II and III), complement activation and inhibition (study II and III), upregulation and inhibition of a granulocyte marker (study II), and studies on bacterial growth and inhibition of the growth (study II).…”
Section: Pig In Vitro Serum and Whole Blood Modelsmentioning
confidence: 99%